Role of salt concentration in blend polymer for energy storage conversion devices - Arya A.; Sadiq M.; Sharma A.L. (My University, 2025)
Solid Polymer Electrolytes (SPE) are materials of considerable interest worldwide, which serves dual purpose of electrolyte and separator between electrode compartments in renewable energy conversion/storage devices such as; high energy density batteries, electrochromic display devices, and supercapacitors. Polymer blend electrolytes are prepared for various concentration of salt (Ö/Li) with the constant ratio (0.5 gm) of each PEO and PAN polymers (blend polymer) using solution casting technique. Solid polymeric ionic conductor as a separator is the ultimate substitute to eliminate the drawback related to liquid and gel polymer ionic conductors. In the present work, solid polymer electrolyte film consisting of PEO, PAN and LiPF6 are examined for various concentration of lithium salt by keeping PEO/PAN blend ratio as a constant with a view to optimize the dominant salt concentration which could give the maximum conductivity at ambient temperature. © 2016 Author(s).